2023
DOI: 10.1021/acscentsci.2c01449
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to the Discovery of Protein–Protein Interaction Stabilizers

Abstract: Dysregulation of protein–protein interactions (PPIs) commonly leads to disease. PPI stabilization has only recently been systematically explored for drug discovery despite being a powerful approach to selectively target intrinsically disordered proteins and hub proteins, like 14-3-3, with multiple interaction partners. Disulfide tethering is a site-directed fragment-based drug discovery (FBDD) methodology for identifying reversibly covalent small molecules. We explored the scope of disulfide tethering for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…14-3-3 proteins are not bona fide transcription factors as they do not contain DNA-binding domains (32). With the ability of 14-3-3 proteins to interact with metabolic transcription factors, such as FOXO1 and the CREB coactivators CRTCs (33, 34), it seemed plausible that 14-3-3ζ may influence the differentiation of preadipocytes by binding to and nucleating adipogenic transcriptional complexes. In fact, we previously showed that 14-3-3ζ interacts with C/EBP-β during adipogenesis(9).…”
Section: Resultsmentioning
confidence: 99%
“…14-3-3 proteins are not bona fide transcription factors as they do not contain DNA-binding domains (32). With the ability of 14-3-3 proteins to interact with metabolic transcription factors, such as FOXO1 and the CREB coactivators CRTCs (33, 34), it seemed plausible that 14-3-3ζ may influence the differentiation of preadipocytes by binding to and nucleating adipogenic transcriptional complexes. In fact, we previously showed that 14-3-3ζ interacts with C/EBP-β during adipogenesis(9).…”
Section: Resultsmentioning
confidence: 99%
“…Systematic technologies geared towards the identification of native PPI stabilizers [11][12][13] tend to be target-directed, compared to cell-based technologies for molecular glue degraders. [14][15][16] For instance, we have established biochemical fragment-based assays for the identification, validation, and optimization of PPI stabilizers.…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…Our workflow employs a mass spectrometry (MS)based site-directed disulfide tethering approach that has identified highly cooperative stabilizers for multiple 14-3-3/client complexes. 11,12,17 During chemical optimization, PPI stabilizers are evaluated using MS-and fluorescence anisotropy (FA)-based assays. These technologies measure stabilization of 14-3-3 and a peptide derived from the client protein, facilitating screening and x-ray crystallography.…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
“…60,61 We recently expanded the disulfide-tethering study to develop 14-3-3σ/client glues for peptides with diverse shapes and binding modes. 62 The native Cys38 at the periphery of the peptide-binding groove on 14-3-3σ (Figure 1A) was targeted with a library consisting of ∼1600 disulfide fragments. Both client-selective and broadly stabilizing fragments were identified.…”
Section: ■ Introductionmentioning
confidence: 99%